Study on the preparation and design of chenille/polyester integrated yarns and its acoustic properties - Xin He; Mengfan Hu; Gonghai Wang; Shaoju Fu (Scientific Reports)
Abstract With the rapid development of industrialization and urbanization, the impact of noise on people’s health has become an increasingly serious issue, but it is still a challenge for the reducing the noise due to its complex property. Textiles with many loose porous structures have gained much significant attentions, thus chenille yarns with plush fibers on the surface, and polyester monofilament were chosen to fabricate the integrated knitting yarns, and their fundamental and mechanical properties were fully evaluated. The results showed that the diameter and braiding angle of the blended yarns decreased with the increase of pitch, resulting in a linear correlation of R2 > 0.8. The breaking strength values of the 3 + 1 series were much lower than that of the 4 + 1 series, while the force utilization rates of the 3 + 1 series were much higher than that of the 4 + 1 series, with a force utilization rate of 98%. Moreover, the dynamic friction coefficient of the 3 + 1 series integrated yarns were much lower than that of the 4 + 1 series, and that of the 4 + 1 series integrated yarns exhibited the lowest bending stiffness, indicating that these two kinds of yarns were the most suitable for the potential application of sound absorption.